Lithium ion battery
By adding specific boron compounds to the electrolyte of lithium-ion batteries and using cobalt oxygen layered oxides of O2 phase in the positive electrode active material, the two are coordinated to solve the energy density of lithium-ion batteries at high voltage. Capacity and cycle performance issues achieve higher battery performance and longer cycle life.
Patent Information
- Application Number
- CN202411580026.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
How to make lithium-ion batteries have high energy density, high capacity and long cycle life in a high voltage environment to solve the problems of structural stability and energy loss.
A specific boron compound is added to the electrolyte of a lithium-ion battery, and a cobalt oxygen layered oxide of O2 phase is used in the positive electrode active material, so that the two can coordinate with each other, stabilize the material structure and improve ion transport efficiency.
It realizes that lithium-ion batteries have high energy density, capacity and cycling performance under high voltage, reduces the risk of cracks in electrode materials and the oxidation and decomposition of electrolytes, and improves the overall performance of the battery.
Smart Images

Figure CN119419371A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in aerospace, energy storage, electric vehicles, portable electronic devices (such as mobile phones, tablets, laptops) and other fields due to their advantages such as no memory effect, low self-discharge efficiency, environmental protection and non-toxicity, and lightweight. With the development of science and technology, traditional battery technology has been unable to meet the needs of some high-energy consumption equipment and applications, and has put forward higher requirements on battery life. Improving energy density is one of the effective ways to improve battery life.
[0003] At present, the energy density of the battery is generally effectively improved by increasing the cut-off charging voltage of the active material. Under the same volume or weight, more electrical energy can be stored and more electricity can be released in a shorter time. However, under high voltage, the structural stability of the O2 phase cobalt oxygen layered oxide is poor, and it may even cause cracks in the electrode material. The electrolyte will also undergo oxidative decomposition under high voltage, which will have a negative impact on the cycle stability of the battery. At the same time, under high voltage, it will also cause more energy loss during the charging and discharging process, affecting the battery capacity.
[0004] Therefore, how to make lithium-ion batteries have high energy density, high capacity and long cycle life under high voltage environment is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] In view of the above-mentioned defects, the present invention provides a lithium-ion battery, in which the electrolyte includes a specific boron compound, and the positive electrode active material includes an O2-phase cobalt oxygen layered oxide. The two work together to enable the lithium-ion battery to have higher energy density, capacity and cycle performance under high voltage environment.
[0006] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material;
[0007] The electrolyte includes a boron compound, and the boron compound includes one or more compounds represented by Formula I, Formula II, Formula III, and Formula IV:
[0008]
[0009] In Formula IV, R1 is selected from C1 to C 10 Hydrocarbon, C1~C 10 Alkoxy, C6~C 10R2 and R3 are each independently selected from one of a hydrogen atom, a C1-C6 hydrocarbon group, a C1-C6 alkoxy group and an oxo group;
[0010] The positive electrode active material includes a cobalt oxygen layered oxide in an O2 phase.
[0011] Furthermore, the lithium-ion battery satisfies 0<x / (z+y)≤1.3;
[0012] Wherein, x is the mass content of the boron compound in the electrolyte, in %; y is the cobalt oxygen interlayer spacing of the cobalt oxygen layered oxide of the O2 phase, and z is the lithium oxygen interlayer spacing, in
[0013] Preferably, 0.1≤x≤6, and / or, 2.0≤y≤2.1, and / or, 2.6≤z≤2.8.
[0014] Furthermore, the lithium cobalt layered oxide has a structural formula shown in Formula 1 or Formula 2:
[0015] Li n-c Na c Co d M1 b M2 a O2 Formula 1
[0016] In formula 1, 0.6≤n≤0.8, 0<c≤0.05, 0≤a≤0.1, 0≤b≤0.1, 0.8≤d≤1, 0≤b / d<0.1, M1 and M2 include at least one of Te, W, Al, B, P and K;
[0017] Li m-k-j Na k Co 1-i M3 j M4 i O2 Formula 2
[0018] In Formula 2, 0.6≤m≤0.8, 0<k≤0.05, 0≤i≤0.1, 0<j≤0.02, and M3 and M4 include at least one of Te, W, Al, B, P and K.
[0019] Furthermore, with a charge cut-off voltage of 4.55 to 4.65 V and a discharge cut-off voltage of 3.0 V, at a charge and discharge rate within 1C, the number of discharge peaks of the dQ / dV curve of the lithium-ion battery is ≥ 4;
[0020] Preferably, the discharge curve of the lithium-ion battery includes at least three discharge platforms.
[0021] Furthermore, the compound represented by formula IV includes one or more of the following compounds:
[0022]
[0023] Furthermore, the electrolyte further comprises a silicon compound, and the silicon compound has a structure shown in Formula V:
[0024]
[0025] In Formula V, R4, R5, R6, and R7 are independently selected from substituted or unsubstituted C1-C 10 Hydrocarbon, substituted or unsubstituted C1-C 10 Alkyloxy and substituted or unsubstituted C1-C 10 alkylsilyl group, and at least one of R4, R5, R6 and R7 is selected from substituted or unsubstituted unsaturated C2-C 10 Hydrocarbon or substituted or unsubstituted unsaturated C2-C 10 Alkyloxy;
[0026] Preferably, the silicon compound comprises one or more of the following compounds:
[0027]
[0028] Further, based on the total mass of the electrolyte, the mass content of the silicon compound is m%, wherein 0.2≤x+m≤11;
[0029] Preferably, 0.5≤x+m≤8;
[0030] More preferably, 0.1≤m≤5.
[0031] Furthermore, the electrolyte further comprises a sulfonate compound, and the sulfonate compound has a structure shown in Formula VI:
[0032]
[0033] In Formula VI, R8 and R9 are independently selected from one of H, C1-C5 hydrocarbon group, C1-C5 fluorinated hydrocarbon group, and phenyl group, and n is an integer between 1 and 4;
[0034] Preferably, the sulfonate compound comprises one or more of the following compounds:
[0035]
[0036] Further, based on the total mass of the electrolyte, the mass content of the sulfonate compound is n%, wherein 0.2≤x+n≤8;
[0037] Preferably, 0.1≤n≤5.
[0038] Furthermore, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector;
[0039] The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material;
[0040] Preferably, the mass content of silicon in the silicon-carbon material is 1% to 50%;
[0041] More preferably, the average sphericity of the silicon-carbon material is 0.5-1.
[0042] The implementation of the present invention has at least the following advantages:
[0043] The O2-phase cobalt oxygen layered oxide in the lithium-ion battery of the present invention has a larger cobalt oxygen layer spacing and lithium oxygen layer spacing, which can increase the operating voltage of the battery, but the material is prone to phase change under high voltage; and the special boron compounds in the electrolyte can modify the O2-phase cobalt oxygen layered oxide, stabilize the structure of the material and improve its ion transmission efficiency, so that the lithium-ion battery has higher energy density, capacity and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is the discharge capacity retention rate of the lithium ion battery in Example 1 of the present invention at different rates. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, and the positive electrode active material layer comprises a positive electrode active material;
[0047] The electrolyte includes a boron compound, and the boron compound includes one or more compounds represented by Formula I, Formula II, Formula III, and Formula IV:
[0048]
[0049] In Formula IV, R1 is selected from C1 to C 10 Hydrocarbon, C1~C 10 Alkoxy, C6~C 10 R2 and R3 are each independently selected from one of a hydrogen atom, a C1-C6 hydrocarbon group, a C1-C6 alkoxy group and an oxo group;
[0050] The positive electrode active material includes cobalt oxygen layered oxide in an O2 phase.
[0051] The present invention allows the electrolyte to include at least one boron compound among the compounds shown in Formula I, Formula II, Formula III, and Formula IV, and the positive electrode active material includes O2-phase cobalt oxide layered oxide, so that the lithium ion battery can have high energy density, high capacity, and long cycle life under high voltage environment. Based on this phenomenon, the inventor analyzed and believed that the reason may be: usually under high voltage conditions, the interaction between charges and polarization effects inside the electrode material will be enhanced, and the O2-phase cobalt oxide layered oxide in the present application has a larger cobalt oxide interlayer spacing and lithium oxide interlayer spacing, so it can reduce the interaction between charges and reduce the polarization effect, so that the battery can work stably under high voltage; however, the O2-phase cobalt oxide layered oxide is prone to phase change under high voltage, and accompanied by a drastic change in the volume of the material, it is easy to cause cracks in the electrode, and the boron compound with the above structure can form a complex with the metal ions in the O2-phase cobalt oxide layered oxide to stabilize the positive electrode activity. The structure of the material, on the one hand, can provide additional mechanical support for the O2 phase cobalt oxide layered oxide, effectively improve the cracks caused by structural changes during the cycle charge and discharge process, and further avoid the problem of battery short circuit or leakage; on the other hand, it helps to maintain the integrity and stability of the lithium ion transmission channel inside the O2 phase cobalt oxide layered oxide, so that lithium ions can be transmitted more efficiently, thereby improving the battery's discharge platform; at the same time, boron compounds can form a protective layer on the surface of the O2 phase cobalt oxide layered oxide, and the protective layer has a low diffusion energy barrier, which can improve the ion transmission efficiency and reduce the energy loss during the charge and discharge process, thereby effectively improving the battery capacity. Therefore, when the electrolyte in the lithium-ion battery includes a boron compound with the above structure and an O2 phase cobalt oxide layered oxide, the two work together to comprehensively improve the energy density, capacity and cycle performance under high voltage.
[0052] In addition, since the O2 phase cobalt oxygen layered oxide has a larger cobalt oxygen layer spacing and lithium oxygen layer spacing, it can also provide more movement space for ions in the material, improve the kinetic process of the electrochemical reaction, increase the ion diffusion rate, and improve the battery's rate performance.
[0053] In the present invention, "C1 to C 10The term "hydrocarbon group" refers to a straight-chain or branched hydrocarbon group containing 1 to 10 carbon atoms. The hydrocarbon group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group, wherein an unsaturated chain hydrocarbon group refers to a chain hydrocarbon group containing a double bond or a triple bond, such as an alkene group or an alkyne group. It should be noted that when it is an alkene group or an alkyne group, the number of carbon atoms is 2 to 10; for example, a saturated chain hydrocarbon group may be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, , n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, etc.; the unsaturated chain hydrocarbon group can be vinyl, allyl, 1-methyl-2-propenyl, 2-methyl-2-propenyl, 2-butenyl, 3-butenyl, 1-methyl-3-butenyl, 1-methyl-2-butenyl, etc.; the alkynyl group can be propargyl, 2-butynyl, 3-butynyl, 1-methyl-3-butynyl, etc.
[0054] Likewise, "C1-C6 hydrocarbon group" refers to an alkoxy branched hydrocarbon group or a branched hydrocarbon group containing 1 to 6 carbon atoms, and the hydrocarbon group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group.
[0055] In the present invention, "C1 to C 10 The "alkoxy group" refers to an alkoxy group containing 1 to 10 carbon atoms, and the "C1 to C6 alkoxy group" refers to an alkoxy group containing 1 to 6 carbon atoms.
[0056] In the present invention, "C6~C 10 The term "aryl group" refers to an aryl group containing 6 to 10 carbon atoms.
[0057] The lithium cobalt layered oxide of the O2 phase in the present invention has a cubic Cmca group, and has characteristic diffraction peaks at 2θ of 17.9° to 18.1° and 67.0° to 67.5° in its XRD spectrum.
[0058] The cobalt oxygen interlayer spacing of the O2 phase cobalt oxygen layered oxide in the present invention and the distance between lithium and oxygen layers It can be obtained by conventional methods in the art. For example, by testing the cobalt oxide layered oxide by XRD, a test spectrum is obtained. Combining the Bragg equation 2d*sinθ=nλ, it can be calculated and Among them, d is the interlayer distance, θ is the diffraction angle, λ is the wavelength of the X-ray, and n is the diffraction order.
[0059] The present invention does not specifically limit the sources of the lithium cobalt layered oxide and the boron compound of the positive electrode active material O2 phase, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.
[0060] In a specific embodiment, the lithium ion battery satisfies 0<x / (z+y)≤1.3; wherein x is the mass content of the boron compound in the electrolyte, in %; y is the cobalt oxygen interlayer spacing of the cobalt oxygen layered oxide in the O2 phase, and z is the lithium oxygen interlayer spacing, in In this range, boron compounds and O2-phase lithium cobalt layered oxides can better cooperate, further reduce the interaction between charges, reduce polarization effects, and increase the cut-off charge voltage; at the same time, boron compounds can also better stabilize the structure of the positive electrode active material, and form a sufficient protective layer on the positive electrode surface to ensure the transmission efficiency of lithium ions, further reducing the energy loss during charging and discharging; and can also provide more mobile space for ion diffusion, improving ion diffusion efficiency; in addition, it can also avoid excessive boron compounds causing ion transmission channel blockage, reducing ion transmission efficiency, and avoid boron compounds from forming too many borides or boron oxides in O2-phase cobalt oxygen layered oxides, causing lattice distortion or structural defects in O2-phase cobalt oxygen layered oxides, deteriorating the structural stability of electrode materials, and reducing the overall performance of the battery. Therefore, when lithium-ion batteries meet 0≤x / (z+y)≤1.3, the battery can have higher energy density, capacity, rate performance and cycle performance.
[0061] Illustratively, x / (z+y) is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or 1.3.
[0062] Preferably, 0.1≤x≤6, and / or, 2.0≤y≤2.1, and / or, 2.6≤z≤2.8.
[0063] Illustratively, x% is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.
[0064] For example, for or
[0065] For example, for or
[0066] In a specific embodiment, the cobalt oxide layer has a structural formula shown in Formula 1 or Formula 2:
[0067] Li n-c Na c Co d M1 b M2a O2 Formula 1
[0068] In formula 1, 0.6≤n≤0.8, 0<c≤0.05, 0≤a≤0.1, 0≤b≤0.1, 0.8≤d≤1, 0≤b / d<0.1, M1 and M2 include at least one of Te, W, Al, B, P and K;
[0069] Li m-k-j Na k Co 1-i M3 j M4 i O2 Formula 2
[0070] In Formula 2, 0.6≤m≤0.8, 0<k≤0.05, 0≤i≤0.1, 0<j≤0.02, and M3 and M4 include at least one of Te, W, Al, B, P and K.
[0071] It should be noted that M1 and M2 are different, and each is independently selected from at least one of Te, W, Al, B, P and K; M3 and M4 are different, and each is independently selected from at least one of Te, W, Al, B, P and K.
[0072] When the cobalt oxide layered oxide has the structure shown in Formula 1 or Formula 2, it is doped with sodium elements (replacing the position of lithium ions). During the charge and discharge process, due to the electrochemical inertness of sodium ions, sodium ions do not participate in the deintercalation reaction, and can play a role in supporting the delithiation positive electrode active material, improve the structural stability of the material, and have little effect on the capacity of the positive electrode active material; and M1, M2, M3 or M4 can replace atoms in the material lattice or fill vacancies, introduce additional free electrons or holes, thereby changing the material's electrical conductivity and ion transmission efficiency, and improving the battery's cycle performance. At the same time, the cobalt oxide layered oxide having the aforementioned structural formula can also better cooperate with boron compounds to further improve the structural stability and ion transmission efficiency of the positive electrode active material, so that the battery has higher capacity and cycle performance.
[0073] In a specific embodiment, with a charge cut-off voltage of 4.55 to 4.65 V and a discharge cut-off voltage of 3.0 V, at a charge and discharge rate within 1 C, the number of discharge peaks of the dQ / dV curve of the lithium-ion battery is ≥4.
[0074] Since the positive electrode active material O2 phase cobalt oxide layered oxide in the present invention is more prone to phase change under high voltage compared with conventional lithium cobalt oxide, the electrochemical reaction inside the battery during discharge is also more complex, which helps to make fuller use of the energy inside the battery; however, when the battery is overcharged or the negative electrode material is insufficient, the lithium ions in the O2 phase cobalt oxide layered oxide may be deposited as metallic lithium on the negative electrode surface, and these metallic lithiums no longer participate in the subsequent charge and discharge cycles, resulting in a decrease in the number of active lithium ions, thereby affecting the number of discharge peaks. When the number of discharge peaks of the dQ / dV curve obtained by the lithium-ion battery under the above-mentioned charge and discharge conditions is ≥4, it means that there is no obvious shift in the discharge peak position of the battery, proving that boron compounds and O2 phase cobalt oxide layered oxide can work well together, effectively improve the structural stability of the O2 phase cobalt oxide layered oxide, and have good cycle performance at a higher charge and discharge efficiency.
[0075] The dQ / dV curve in the present invention is obtained by first-order differentiation of the charge and discharge curve of the lithium-ion battery, wherein the charge and discharge curve is obtained when the lithium-ion battery is charged to 100% SOC at a rate within 1C with a charge cut-off voltage of 4.55V to 4.65V and a rate within 1C, and then discharged to a discharge cut-off voltage of 3.0V at a rate within 1C; under the premise that the number of cycles is not more than 10, the number of discharge peaks of the dQ / dV curve of the lithium-ion battery is ≥4. The preparation method of the lithium-ion battery is:
[0076] In an environment with a dew point below -10°C, the positive electrode active material, polyvinylidene fluoride (PVDF), SP (superP) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain a surface density of 0.012 g / cm 2 , compacted density is 4.2g / cm 3 The negative electrode active materials artificial graphite, silicon carbon material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 80:14.5:2.5:1.5:1:0.5, deionized water was added, and the negative electrode active slurry was obtained under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of the copper foil; the coated copper foil was dried at room temperature, then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a surface density of 0.006 g / cm 2 , compacted density is 1.7g / cm 3The positive electrode sheet, the negative electrode sheet and the separator are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wound to obtain a battery cell, the battery cell is placed in an outer packaging aluminum foil, the prepared electrolyte (including the above-mentioned boron compound) is injected into the outer packaging, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, shaping, sorting and other processes.
[0077] In a specific embodiment, the discharge curve of the lithium-ion battery includes at least three discharge platforms. At this time, the positive electrode active material is more likely to undergo phase change under high voltage, thereby changing the crystal structure and electronic state of the positive electrode active material, which helps to more fully utilize the energy inside the battery; at the same time, the boron compounds in the electrolyte can also stabilize the structure of the positive electrode active material, effectively improving the problem of electrode cracking, thereby further improving the battery capacity and cycle performance.
[0078] The discharge curve of the lithium ion battery in the present invention is obtained by charging the lithium ion battery at a charge cutoff voltage of 4.55V to 4.65V at a rate within 1C to a SOC of 100%, and then discharging the lithium ion battery at a rate within 1C to a discharge cutoff voltage of 3.0V.
[0079] In one embodiment, the compound represented by formula IV includes one or more of the following compounds:
[0080]
[0081] When the compound shown in Formula IV includes the above-mentioned compound, it can better cooperate and coordinate with the O2 phase lithium cobalt layered oxide, further improve the energy density, capacity and cycle performance of the battery, and ensure higher rate performance.
[0082] When the compound shown in the aforementioned IV includes a plurality of specific compounds among the aforementioned compounds, the present invention does not specifically limit the ratio between the specific compounds.
[0083] In a specific embodiment, the electrolyte further includes a silicon compound having a structure shown in Formula V:
[0084]
[0085] In Formula V, R4, R5, R6, and R7 are independently selected from substituted or unsubstituted C1-C 10 Hydrocarbon, substituted or unsubstituted C1-C 10 Alkyloxy and substituted or unsubstituted C1-C 10 alkylsilyl group, and at least one of R4, R5, R6 and R7 is selected from substituted or unsubstituted unsaturated C2-C 10 Hydrocarbon or substituted or unsubstituted unsaturated C2-C10 Alkyloxy;
[0086] Preferably, the silicon compound comprises one or more of the following compounds:
[0087]
[0088] During the charging process, as the potential of the positive electrode active material gradually increases, it is easy to catalyze the oxidation and decomposition of the electrolyte, and the harmful substances produced will corrode and damage the structure of the negative electrode material; and the decomposition of the electrolyte will also form an unstable SEI film on the surface of the negative electrode, affecting the insertion and extraction process of lithium ions and reducing the ion migration efficiency. At the same time, since boron compounds can effectively improve the ion transmission efficiency of the O2 phase cobalt oxygen layered oxide, the negative electrode should also have a matching ion transmission capacity, otherwise it will cause lithium ions to deposit on the surface of the negative electrode, causing lithium deposition at the negative electrode, affecting the battery cycle performance and safety performance.
[0089] The present invention adds the silicon compound of the above structure to the electrolyte, which can cooperate with the boron compound to preferentially form an organic SEI film on the surface of the negative electrode. On the one hand, it can effectively prevent direct contact between the electrolyte and the negative electrode material, not only reducing the possibility of electrolyte decomposition under high voltage, but also reducing the generation of harmful substances in the electrolyte, preventing them from corroding and damaging the negative electrode material; on the other hand, it can affect the electron distribution on the electrode surface, play a role in regulating the surface potential of the negative electrode, and reduce the reaction activity between the negative electrode and the electrolyte; on the other hand, the formed SEI film also has a higher ion transfer efficiency, can better adapt to the positive electrode, and effectively prevent lithium precipitation at the negative electrode; and the SEI film also has a higher elasticity, can well adapt to the expansion of the negative electrode active material, and prevent the SEI film from rupture.
[0090] In addition, the silicon compound can also form a CEI film on the positive electrode surface, improve the wettability of the positive electrode active material, improve the ion conductivity of the battery, and prevent the positive electrode active material from directly contacting with harmful substances in the electrolyte to cause side reactions.
[0091] In summary, when the electrolyte also includes the silicon compound of the above structure, and further includes at least one compound of Formula V-1 to Formula V-8, it can effectively protect the positive and negative electrodes, significantly reduce the thermal runaway of the battery caused by heat generated by side reactions, thereby effectively improving the hot box safety performance and rate performance of the battery at high voltage.
[0092] The "substituted or unsubstituted C1-C10 hydrocarbon group" in the present invention refers to a substituted or unsubstituted straight-chain hydrocarbon group or branched hydrocarbon group containing 1 to 10 carbon atoms. The hydrocarbon group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. It should be noted that when it is an olefin group or an alkyne group, the number of carbon atoms is 2 to 10. The substituents include at least one of trimethylsilyl, hydroxyl, amino, and halogen atoms (F, Cl, Br, I), and any hydrogen atom in the hydrocarbon group can be replaced by a trimethylsilyl, hydroxyl, amino, or halogen atom, and the number of substituents is not limited; when the substituent is specified as a group with a specific carbon number, all geometric isomers with that carbon number are included. The halogen atom here refers to
[0093] In the present invention, the "substituted or unsubstituted C1-C 10 "Hydrocarbyloxy" refers to a substituted or unsubstituted straight-chain or branched hydrocarbonoxy group containing 1 to 10 carbon atoms; a hydrocarbonoxy group refers to a hydrocarbon group and an oxygen atom, usually represented by RO-, wherein R represents a hydrocarbon group; the hydrocarbon group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group, such as an olefin group or an alkyne group. It should be noted that when it is an olefin group or an alkyne group, the number of carbon atoms is 2 to 10. Exemplarily, the hydrocarbonoxy group includes a methoxy group (CH3O-), an ethoxy group (C2H5O-), a propoxy group (C3H7O-), etc. The substituents include at least one of a hydroxyl group, an amino group, and a halogen atom (F, Cl, Br, I), and any hydrogen atom in the hydrocarbon group may be substituted by a hydroxyl group, an amino group or a halogen atom, and the number of substituents is not limited; when the substituent is specified as a group with a specific carbon number, all geometric isomers with that carbon number are included.
[0094] The "substituted or unsubstituted C1-C10 alkylsilyloxy group" in the present invention refers to a substituted or unsubstituted alkylsilyloxy group containing 1 to 10 carbon atoms; an alkylsilyloxy group refers to a silyloxy group substituted by an alkyl group, wherein the substituent includes at least one of a hydroxyl group, an amino group, and a halogen atom (F, Cl, Br, I), and any hydrogen atom in the hydrocarbon group can be replaced by a hydroxyl group, an amino group or a halogen atom, and the number of substituents is not limited; when the substituent is specified as a group with a specific carbon number, all geometric isomers with that carbon number are included.
[0095] When the silicon-based compound includes multiple specific compounds of the aforementioned compounds at the same time, the present invention does not specifically limit the ratio between the specific compounds.
[0096] The present invention does not limit the specific source of the silicon compound, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0097] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the silicon compound is m%, wherein 0.2≤x+m≤11, preferably, 0.5≤x+m≤8, and more preferably, 0.1≤m≤5. When the mass content m% of the silicon compound in the electrolyte and the mass content x% of the boron compound satisfy the aforementioned relationship, and further, when m is within the aforementioned range, the thickness of the CEI film and the SEI film is relatively moderate. On the one hand, sufficient protection can be provided to the positive and negative electrodes, so that the battery can operate stably at high voltage; on the other hand, the increase in internal resistance caused by excessive film formation can be effectively avoided, which can not only slow down battery aging and extend the cycle life of the battery, but also reduce heat generation during charging and reduce the risk of thermal runaway.
[0098] Illustratively, x+m is 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8.
[0099] Illustratively, m% is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0100] In a specific embodiment, the electrolyte further includes a sulfonate compound, and the sulfonate compound has a structure shown in Formula VI:
[0101]
[0102] In Formula VI, R8 and R9 are independently selected from one of H, C1-C5 hydrocarbon group, C1-C5 fluorinated hydrocarbon group, and phenyl group, and n is an integer between 1 and 4;
[0103] Preferably, the sulfonate compound comprises one or more of the following compounds:
[0104]
[0105] When the electrolyte also includes a sulfonate additive having the above structure, the sulfonate additive can cooperate with the boron compound and work together. On the one hand, it can form a complex with metal ions such as lithium ions in the O2 phase cobalt oxide layered oxide to reduce its reaction activity, thereby reducing the precipitation and deposition of lithium on the electrode surface, inhibiting the growth of lithium dendrites, and improving the safety of the battery; on the other hand, the sulfonate additive can also react with the water in the electrolyte, competing with the water for the combination with key ions such as lithium ions, thereby reducing the adverse effect of water on the battery performance; on the other hand, when the electrolyte contains fluorine, hydrofluoric acid will be produced during the circulation process, and the sulfonate additive can form a stable compound with it, reducing the corrosion of hydrofluoric acid on the negative electrode of the battery, and improving the cycle stability and safety of the battery.
[0106] In addition, the sulfonate additives in the electrolyte can also form an inorganic SEI film with high mechanical strength on the surface of the negative electrode, which helps prevent lithium dendrites from piercing the SEI film and causing electrolyte consumption, further improving the battery's cycle performance.
[0107] It should be noted that when n is 1, the compound represented by Formula VI includes a five-membered ring, when n is 2, it includes a six-membered ring, when n is 3, it includes a seven-membered ring, and when n is 4, it includes an eight-membered ring.
[0108] When the aforementioned sulfonate additives include multiple specific compounds of Formula VI-1 to Formula VI-8 at the same time, the present invention does not specifically limit the ratio of the multiple specific compounds.
[0109] The present invention does not limit the specific source of the sulfonate additives, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0110] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the sulfonate additive is n%, wherein 0.2≤x+n≤8, preferably, 0.1≤n≤5. When the mass content of the sulfonate additive in the electrolyte and the mass content of the boron compound satisfy the aforementioned relationship, and n further satisfies the aforementioned range, the sulfonate additive and the boron compound can be better coordinated, further inhibiting the occurrence of side reactions, and improving the cycle stability and safety of the battery; at the same time, it can also ensure that the electrolyte has a high electrical conductivity, reduce the internal resistance of the battery, and improve the charge and discharge efficiency. When x+n is too high, the SEI film on the surface of the negative electrode will be too thick, increasing the interface impedance and reducing the ion transfer efficiency, thereby causing lithium precipitation on the surface of the negative electrode.
[0111] Illustratively, x+n is 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8.
[0112] Illustratively, n% is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0113] In a specific embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector;
[0114] The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material;
[0115] Preferably, the mass content of silicon in the silicon-carbon material is 1% to 50%;
[0116] More preferably, the average sphericity of the silicon-carbon material is 0.5-1.
[0117] When the negative electrode active material includes silicon-carbon material, the high energy density and cycle stability of the battery can be effectively improved. However, there is a large volume expansion and contraction during the charge and discharge process, which will cause the silicon to break and pulverize. The boron compounds in the electrolyte help the negative electrode to form a stable SEI film, improving the effect of the volume change of the silicon-carbon material during the charge and discharge process on the battery performance. The SEI film formed has excellent ionic conductivity and chemical stability, and can serve as a fast channel for ion transmission, reducing the transmission resistance of ions on the electrode surface and improving the ion mobility.
[0118] At the same time, because the ion transmission efficiency of the O2 phase cobalt oxygen layered oxide is greatly improved under the action of boron compounds, a large amount of lithium ions are released from the positive electrode during the charging process under high voltage. If the lithium ions cannot be embedded in the negative electrode in time, lithium deposition will occur at the negative electrode, affecting the cycle performance and safety performance of the battery. Therefore, the present invention selects silicon-carbon material as the negative electrode active material to provide sufficient lithium insertion sites to effectively avoid the problem of lithium deposition under high voltage.
[0119] In addition, boron compounds can also react with other components in the electrolyte to form more stable compounds. These stable compounds can reduce the reactivity of the electrolyte, reduce its decomposition rate on the surface of the silicon-carbon negative electrode, and reduce the generation of harmful by-products, thereby extending the cycle life of the battery.
[0120] Furthermore, when the mass content of silicon in the silicon-carbon material is 1% to 50%, the battery can have a higher energy density, and the carbon material therein can act as a buffer layer to absorb the stress generated by silicon during the charging and discharging process, effectively alleviating the volume expansion effect of silicon, thereby improving the cycle stability of the battery.
[0121] Furthermore, when the average sphericity of the silicon-carbon material is 0.5 to 1, the silicon-carbon material has a higher sphericity, which can make the material expand and contract more evenly during the charge and discharge process, reduce the electrode breakage and pulverization caused by volume change, thereby reducing the loss of active materials and improving the electrochemical stability of the battery; at the same time, it can also avoid the loss of lithium insertion sites caused by the loss of active materials, and can provide sufficient lithium insertion sites during the charging process, further avoiding the occurrence of lithium precipitation. Moreover, the contact area between the silicon-carbon material and the electrolyte can be made relatively uniform, which helps to improve the interface properties, reduce the interface resistance, improve the charge transfer efficiency, and also help to form a more uniform and stable solid electrolyte interface film (SEI film), thereby improving the cycle stability and rate performance of the battery.
[0122] The structure of the silicon-carbon material in the present invention is coated, embedded or doped, wherein the coated silicon-carbon material is obtained by coating carbon material on the surface of silicon material, which can effectively alleviate the volume expansion of silicon; the embedded silicon-carbon material is formed by embedding silicon particles into a carbon matrix to form secondary particles; the doped silicon-carbon material is a composite material formed by doping silicon material with carbon material.
[0123] In the present invention, coated silicon-carbon materials and embedded silicon-carbon materials are preferred.
[0124] The average sphericity in the present invention can be obtained by testing using the following method:
[0125] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode plate is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the plate, and then the negative electrode active material layer is washed off from the plate with deionized water, and the filtrate is removed by centrifugation after ultrasonic treatment and then dried. The obtained powder is observed in the backscattering mode of a scanning electron microscope. In this mode, the contrast of silicon-carbon particles is brighter, which can be distinguished from graphite and conductive carbon. The image of each particle with brighter contrast in the SEM photo under a certain magnification (such as 2500 times) is analyzed by image processing software (such as ImagePro Plus) to obtain the perimeter and area of each particle, and the perimeter equivalent radius r1 and area equivalent radius r2 of each particle are calculated respectively, then the sphericity S of each particle is r2 / r1, and then the sphericity of each particle is weighted averaged by quantity, that is, the average sphericity of the silicon-carbon material in the negative electrode plate is obtained.
[0126] Exemplarily, the mass content of silicon in the silicon-carbon material is 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0127] Illustratively, the average sphericity of the silicon carbon material is 0.5, 0.6, 0.7, 0.8, 0.9 or 1.
[0128] The lithium-ion battery of the present invention is described in detail below through specific embodiments.
[0129] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0130] Example 1
[0131] This embodiment provides a lithium ion battery, and the preparation method thereof comprises the following steps:
[0132] 1) Preparation of positive electrode
[0133] The positive electrode active material Li 0.7 Na 0.002 Co 0.96 W 0.02 Te 0.02 O2, polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of the aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain a positive electrode sheet with a surface density of 0.012 and a compaction density of 4.2;
[0134] Among them, lithium cobalt oxide has a cubic Cmca group, and has characteristic diffraction peaks of 2θ of 17.9°~18.1° and 67.0°~67.5° in its XRD spectrum, and the cobalt oxygen layer spacing is The distance between lithium-oxygen layers is
[0135] 2) Negative electrode preparation
[0136] The negative electrode active materials artificial graphite, silicon-carbon material (silicon mass content is 25%, average sphericity is 0.8), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 80:14.5:2.5:1.5:1:0.5, deionized water is added, and a negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on both surfaces of a copper foil; the coated copper foil is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet with a surface density of 0.006 and a compaction density of 1.7.
[0137] 3) Isolation film
[0138] A 8μm polyethylene / polypropylene composite isolation film is selected.
[0139] 4) Preparation of electrolyte
[0140] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC) / propylene carbonate (PC) / diethyl carbonate (DEC) / propyl propionate (PP) are mixed uniformly in a mass ratio of 10:20:20:50 to obtain an organic solvent; then, 14wt% of fully dried lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte is quickly added thereto, and after dissolution, 0.7% of a boron compound (the compound shown in Formula I) based on the total mass of the electrolyte is added, followed by 1% of a silicon compound (the compound shown in Formula V-4) based on the total mass of the electrolyte, and then 2.5% of a sulfonate compound (the compound shown in Formula VI-1) based on the total mass of the electrolyte is added; after stirring uniformly, the electrolyte is obtained after passing the moisture and free acid tests.
[0141] 5) Preparation of lithium-ion batteries
[0142] The positive electrode sheet prepared in step 1), the negative electrode sheet prepared in step 2), and the separator prepared in step 3) are stacked in the order of positive electrode sheet, separator, and negative electrode sheet, and then wound to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the electrolyte prepared in step 4) is injected into the outer packaging. After vacuum packaging, standing, formation, shaping, sorting and other processes, the lithium-ion battery of this embodiment is obtained; the charge and discharge range of the battery of the present invention is 3.0-4.6V.
[0143] Example 2
[0144] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula I is replaced by the compound represented by Formula II.
[0145] Example 3
[0146] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula I is replaced by the compound represented by Formula III.
[0147] Example 4
[0148] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by formula I is replaced by the compound represented by formula IV-1.
[0149] Example 5
[0150] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula I is replaced by the compound represented by Formula IV-2.
[0151] Example 6
[0152] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula I is replaced by the compound represented by Formula IV-3.
[0153] Example 7
[0154] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula I is replaced by the compound represented by Formula IV-6.
[0155] Example 8
[0156] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass percentage of the compound represented by Formula I in the electrolyte is adjusted to 0.1%.
[0157] Example 9
[0158] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the compound represented by formula I in the electrolyte is adjusted to 6%; the mass content of the compound represented by formula VI-1 in the electrolyte is adjusted to 2%.
[0159] Example 10
[0160] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by formula V-4 is replaced by the compound represented by formula V-1.
[0161] Embodiment 11
[0162] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by formula V-4 is replaced by the compound represented by formula V-2.
[0163] Example 12
[0164] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by formula V-4 is replaced by the compound represented by formula V-5.
[0165] Example 13
[0166] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by formula V-4 is replaced by the compound represented by formula V-8.
[0167] Embodiment 14
[0168] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the compound represented by formula V-4 in the electrolyte is adjusted to 0.1%.
[0169] Embodiment 15
[0170] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the compound represented by formula V-4 in the electrolyte is adjusted to 5%.
[0171] Example 16
[0172] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula VI-1 is replaced by the compound represented by Formula VI-4.
[0173] Embodiment 17
[0174] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula VI-1 is replaced by the compound represented by Formula VI-5.
[0175] Embodiment 18
[0176] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula VI-1 is replaced by the compound represented by Formula VI-7.
[0177] Embodiment 19
[0178] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound represented by Formula VI-1 is replaced by the compound represented by Formula VI-8.
[0179] Embodiment 20
[0180] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the compound represented by Formula VI-1 in the electrolyte is adjusted to 0.1%.
[0181] Embodiment 21
[0182] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the compound represented by Formula VI-1 in the electrolyte is adjusted to 5%.
[0183] Embodiment 22
[0184] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), lithium cobalt oxide is replaced by Li 0.7 Na 0.002 Co 0.95 Al 0.03 Ti 0.02 O2, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0185] Embodiment 23
[0186] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), lithium cobalt oxide is replaced by Li 0.71 Na 0.003 Co 0.95 B 0.02 Al 0.03 O3, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0187] Embodiment 24
[0188] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), lithium cobalt oxide is replaced by Li 0.71 Na 0.003 Co 0.96 P 0.01 Al 0.03 O4, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0189] Embodiment 25
[0190] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), lithium cobalt oxide is replaced by Li 0.71 Na 0.003 Co 0.98 Al 0.02 O5, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0191] Embodiment 26
[0192] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), lithium cobalt oxide is replaced by Li 0.71 Na 0.003 Co 0.98 Al 0.02 O5, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0193] Embodiment 27
[0194] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the silicon mass content of the silicon-carbon material is adjusted to 1%, and the average sphericity is adjusted to 0.5.
[0195] Embodiment 28
[0196] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the silicon mass content of the silicon-carbon material is adjusted to 50%, and the average sphericity is adjusted to 1.
[0197] Embodiment 29
[0198] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 22, except that in step 4), the mass content of the compound represented by formula I in the electrolyte is adjusted to 6.2%; the mass content of the compound represented by formula VI-1 in the electrolyte is adjusted to 0.1%.
[0199] Embodiment 30
[0200] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 4), lithium cobalt oxide is replaced by Li 0.85 Na 0.002 Co 0.96 W 0.02 Te 0.02 O2, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0201] Embodiment 31
[0202] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), Li 0.7 Na 0.002 Co 0.96 W 0.02 Te 0.02 O2 replaced by Li 0.7 Na 0.002 Co 0.93 W 0.05 Te 0.02 O2, the cobalt oxygen layer spacing of this material is The distance between lithium-oxygen layers is
[0203] Embodiment 32
[0204] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the electrolyte does not include silicon compounds, and the mass percentage of the organic solvent in the electrolyte is 82.8%.
[0205] Embodiment 33
[0206] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the silicon compound in the electrolyte is adjusted to 6%, and the mass percentage of the organic solvent in the electrolyte is 76.8%.
[0207] Embodiment 34
[0208] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the boron compound in the electrolyte is adjusted to 5%, and the mass content of the silicon compound is adjusted to 4%, and the mass percentage of the organic solvent in the electrolyte is 74.8%.
[0209] Embodiment 35
[0210] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the electrolyte does not include sulfonate compounds, and the mass percentage of the organic solvent in the electrolyte is 84.3%.
[0211] Embodiment 36
[0212] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the sulfonate compound in the electrolyte is adjusted to 6%, and the mass percentage of the organic solvent in the electrolyte is 78.3%.
[0213] Embodiment 37
[0214] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of the boron compound in the electrolyte is adjusted to 5%, and the mass content of the silicon compound is adjusted to 5%, and the mass percentage of the organic solvent in the electrolyte is 74.5%.
[0215] Embodiment 38
[0216] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 1, except that in step 2), the negative electrode active material does not include silicon-carbon material, and the mass ratio of artificial graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) is 94.5:2.5:1.5:1:0.5.
[0217] Embodiment 39
[0218] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 2), a silicon-carbon material with a silicon mass content of 53% is used.
[0219] Embodiment 40
[0220] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 2), a silicon-carbon material with an average sphericity of 0.4 is used.
[0221] Comparative Example 1
[0222] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that the electrolyte does not include boron compounds, and the mass content of the organic solvent in the electrolyte becomes 82.5%.
[0223] Comparative Example 2
[0224] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that in step 4), the mass content of the boron compound in the electrolyte is adjusted to 7%.
[0225] Comparative Example 3
[0226] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that in step 1), conventional lithium cobalt oxide material (LiCoO2, the cobalt oxygen layer spacing is The distance between lithium-oxygen layers is ) instead of Li 0.7 Na 0.002 Co 0.96 W 0.02 Te 0.02 O2.
[0227] The basic parameters are shown in Tables 1 and 2.
[0228] Table 1
[0229]
[0230]
[0231]
[0232] Table 2
[0233]
[0234]
[0235] Test Case
[0236] The lithium-ion batteries of the above embodiments and comparative examples were tested for the following performances:
[0237] 1. Energy density
[0238] At 25°C, the weight of the batteries in the above embodiments and comparative examples was tested, and then they were charged at a constant current of 1C to a voltage of 4.6V, and then charged at a constant voltage at 4.6V to a current of 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 1C to a voltage of 3.0V, and the discharge capacity (i.e., the initial capacity of the battery) was recorded. The battery energy is the product of the discharge capacity and the average operating voltage of the battery, and the mass energy density (Wh / kg) is the ratio of the battery energy to the battery weight.
[0239] 2. 25℃ Cyclic Performance Test
[0240] The above lithium ion battery was charged at 25°C with a constant current of 1C to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a voltage of 3.0V. This was a charge and discharge cycle. The initial discharge capacity was recorded as C0 (mAh), and N cycles were cycled according to the above charge and discharge mechanism. The discharge capacity and discharge curve when N was 100 cycles were recorded, and the discharge capacity when N was 500 cycles was recorded as C1 (mAh). The cycle capacity retention rate (%) of the lithium ion battery = (C0 / C1) × 100%. The test and calculation results are shown in Table 3.
[0241] 3. dQ / dV and discharge platform test
[0242] Using the Blue Electric Battery Test System, at 25°C, the battery was discharged at 1C to a voltage of 3.0V, then charged at 1C constant current to a voltage of 4.6V, then charged at 4.6V to a current of 0.05C, left to stand for 5 minutes, and then discharged at 1C constant current to a voltage of 3.0V. Use the Blue Electric Test System data processing software to open the test file, select the "voltage-dQ / dV" drawing model, and you can observe the number of discharge peaks. Select the "voltage-time" drawing model to observe the number of discharge platforms.
[0243] 2. Rate performance test
[0244] The lithium sheet was used as the negative electrode, and assembled into a button battery with the positive electrode sheet and the electrolyte in the above embodiments and comparative examples; at 25°C, the assembled button battery was charged at a constant current of 0.1C to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 3.0V, which was a charge and discharge cycle; 10 cycles were cycled at a rate of 0.1C, left to stand for 10 minutes, and the average discharge capacity was recorded as C2 (mAh); then with 4.55-4.65V as the charge cut-off voltage, the battery was cycled at 0.2C, 0.5C, and 1C for 10T in sequence, and the average discharge capacity during the final 10 cycles at 1C was recorded as C3 (mAh); the average discharge capacity retention rate of the battery at 0.1C rate is 100%, then the discharge capacity retention rate of the battery at 1C (%) = (C3 / C2) × 100%; the test and calculation results are shown in Tables 3 and Figure 1 .
[0245] Figure 1 is the capacity retention rate curve of the lithium ion battery at different rates in Example 1 and Comparative Example 3, Figure 1 It can be seen that the capacity retention rate of the lithium ion battery in Example 1 at a higher rate is still at a high level, while the capacity retention rate of the lithium ion battery in Comparative Example 3 at 1.0C is significantly lower than that in Example 1. It can be seen that the lithium ion battery in Example 1 has a higher rate performance than that in Comparative Example 3.
[0246] 3. Crack analysis of positive electrode
[0247] Ten batteries are set up for each embodiment and comparative example. The batteries are charged at 25°C with a constant current of 1C to a voltage of 4.6V, and then charged at a constant voltage of 4.6V to a current of 0.05C, and left to stand for 5 minutes. Five batteries are taken from each embodiment and comparative example for dissection. The number of cracks per unit area on the surface of the positive electrode is observed by SEM test to obtain the initial average number of cracks. The remaining five batteries are then discharged at a constant current of 1C to a voltage of 3.0V, which is a charge and discharge cycle. After the battery has been cycled 500 times according to the aforementioned charge and discharge mechanism, it is fully charged and removed from the stage. The battery is dissected, and the number of cracks per unit area on the surface of the positive electrode is observed by SEM test to obtain the average number of cracks after the cycle. The growth rate of the number of cracks per unit area before and after the cycle is compared, and the growth rate of the number of cracks per unit area (%) = (positive electrode sheet after 500 cycles - initial average number of cracks) / initial average number of cracks × 100%. The test results are shown in Table 3.
[0248] 4. Hot box performance test
[0249] At room temperature of 25°C, the batteries in the embodiments and comparative examples were charged to 4.6V at a constant current of 1C, left to stand for 60 min, and the appearance was checked and photographed; then the batteries were placed in an oven, heated to 132°C±2°C at a rate of 3°C / min and kept for 60 min, and the samples were observed and compared with the photos of the batteries before placement. If there was no leakage, no smoke, no fire, and no explosion, it was recorded as passing the test. Ten samples were tested for each embodiment and comparative example, and the number of passing samples was recorded. The test results are shown in Table 3.
[0250] Table 3
[0251]
[0252]
[0253]
[0254] From Table 3, we can see that:
[0255] The lithium ion batteries in Examples 1 to 40 have higher energy density, capacity and cycle performance than those in Comparative Examples 1 to 3, and also have higher safety performance and rate performance, wherein the lithium ion battery in Example 1 has an energy density of up to 798Wh / kg, a cycle capacity retention rate of 91.7%, a corresponding rate performance of 99.8%, a crack number growth rate of only 0.6%, and a hot box test pass number of 10 / 10PASS, which is significantly higher than the performance of the lithium ion batteries in Comparative Examples 1 to 3. It can be seen that the lithium ion battery of the present invention can have both high energy density, capacity and cycle performance under high voltage environment.
[0256] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material; The electrolyte includes a boron compound, and the boron compound includes one or more compounds represented by Formula I, Formula II, Formula III, and Formula IV: In Formula IV, R1 is selected from C1 to C 10 Hydrocarbon, C1~C 10 Alkoxy, C6~C 10 R2 and R3 are each independently selected from one of a hydrogen atom, a C1-C6 hydrocarbon group, a C1-C6 alkoxy group and an oxo group; The positive electrode active material includes a cobalt oxygen layered oxide in an O2 phase.
2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery satisfies 0<x / (z+y)≤1.3; Wherein, x is the mass content of the boron compound in the electrolyte, in %; y is the cobalt oxygen interlayer spacing of the cobalt oxygen layered oxide of the O2 phase, and z is the lithium oxygen interlayer spacing, in Preferably, 0.1≤x≤6, and / or, 2.0≤y≤2.1, and / or, 2.6≤z≤2.
8.
3. The lithium ion battery according to claim 1 or 2, characterized in that: The cobalt oxide layered oxide of the O2 phase has a structural formula shown in Formula 1 or Formula 2: Li n-c Na c Co d M1 b M2 a O2 type 1 In formula 1, 0.6≤n≤0.8, 0<c≤0.05, 0≤a≤0.1, 0≤b≤0.1, 0.8≤d≤1, 0≤b / d<0.1, M1 and M2 include at least one of Te, W, Al, B, P and K; Li m-k-j Na k Co 1-i M3 j M4 i O2 formula 2 In Formula 2, 0.6≤m≤0.8, 0<k≤0.05, 0≤i≤0.1, 0<j≤0.02, and M3 and M4 include at least one of Te, W, Al, B, P and K.
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: With a charge cut-off voltage of 4.55 to 4.65 V and a discharge cut-off voltage of 3.0 V, at a charge and discharge rate within 1C, the number of discharge peaks of the dQ / dV curve of the lithium-ion battery is ≥ 4; Preferably, the discharge curve of the lithium-ion battery includes at least three discharge platforms.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The compound represented by formula IV includes one or more of the following compounds:
6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The electrolyte further includes a silicon compound having a structure shown in Formula V: In Formula V, R4, R5, R6, and R7 are independently selected from substituted or unsubstituted C1-C 10 Hydrocarbon, substituted or unsubstituted C1-C 10 Alkyloxy and substituted or unsubstituted C1-C 10 alkylsilyl group, and at least one of R4, R5, R6 and R7 is selected from substituted or unsubstituted unsaturated C2-C 10 Hydrocarbon or substituted or unsubstituted unsaturated C2-C 10 Alkyloxy; Preferably, the silicon compound comprises one or more of the following compounds:
7. The lithium-ion battery according to claim 6, characterized in that: Based on the total mass of the electrolyte, the mass content of the silicon compound is m%, wherein 0.2≤x+m≤11; Preferably, 0.5≤x+m≤8; More preferably, 0.1≤m≤5.
8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: The electrolyte further includes a sulfonate compound, and the sulfonate compound has a structure shown in Formula VI: In Formula VI, R8 and R9 are independently selected from one of H, C1-C5 hydrocarbon group, C1-C5 fluorinated hydrocarbon group, and phenyl group, and n is an integer between 1 and 4; Preferably, the sulfonate compound comprises one or more of the following compounds:
9. The lithium-ion battery according to claim 8, characterized in that: Based on the total mass of the electrolyte, the mass content of the sulfonate compound is n%, wherein 0.2≤x+n≤8; Preferably, 0.1≤n≤5.
10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector; The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material; Preferably, the mass content of silicon in the silicon-carbon material is 1% to 50%; More preferably, the average sphericity of the silicon-carbon material is 0.5-1.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and manufacturing method of cathode
CN101689631A
Positive-electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery including the same
CN104518211A
Nonaqueous-electrolyte secondary battery
CN105940534A
Positive electrode material and positive plate and battery comprising positive electrode material
CN115036474A
Electrolyte and lithium ion battery
CN116315086A